Modernist enamels: Composition, microstructure and stability. Issue 4 (April 2020) - Beltrán, Martí; Schibille, Nadine; Brock, Fiona; Gratuze, Bernard; Vallcorba, Oriol; Pradell, Trinitat
Abstract: Coloured enamels from the materials used in Modernist workshops from Barcelona were produced and compared to those found in the buildings to explore the reason for the reduced stability of the blue and green enamels. They were made of a lead-zinc borosilicate glass with a low softening point, reasonable stability to corrosion and matching thermal expansion coefficient with the blown base glass, mixed with colourants and pigment particles. The historical enamels show a lead, boron and zinc depleted silica rich amorphous glass, with precipitated lead and calcium sulphates or carbonates, characteristic of extensive atmospheric corrosion. The blue and green enamels show a heterogeneous layered microstructure more prone to degradation which is augmented by a greater heating and thermal stress affectation produced by the enhanced Infrared absorbance of blue tetrahedral cobalt colour centres and copper ions dissolved in the glass and, in particular, of the cobalt spinel particles.